3D printed recoverable honeycomb composites reinforced by continuous carbon fibers. (15th July 2021) - Cheng, Yunyong; Li, Junjie; Qian, Xiaoping; Rudykh, Stephan
Abstract: This paper reports the failure and recovery mechanisms of 3D-printed lightweight honeycomb composites. Through this experimental study, we demonstrate the enhanced mechanical performance of 3D-printed composite structures and their ability for shape recovery under heat excitation. The remarkable mechanical performance of the reinforced honeycombs draws from the combination of the structural geometry and the tailored material composition. The results show that the addition of continuous fibers enables the honeycomb structure to avoid catastrophic failure even at high levels of deformation, which allows the shape memory effect to be activated and nearly 87% percent of the initial structural shape to be recovered. Moreover, the reinforced honeycombs exhibit enhanced properties: the specific energy absorption and specific stiffness of the reinforced honeycombs are up to 2 times greater than those of the conventional honeycombs. These enhanced mechanical properties combined with the controllable shape recovery of the 3D-printed structures can be used in the design of novel energy absorbing and protective material systems, biomedical devices, and actuators.